Bridging national and provincial targets: Quantitative evidence for emissions reduction accountability in Korean provinces - Jeon, Seungho; Roh, Minyoung; Kim, Muntae; Kim, Suduk (Energy Strategy Reviews, 2023)
As an international collective action to stop global warming, most nations submitted their Nationally Determined Contributions (NDCs) to the United Nations Framework Convention on Climate Change (UNFCCC). To help ensure consistency and comparability of data between different countries, guidelines are provided by Intergovernmental Panel on Climate Change (IPCC). Likewise, subnations would develop their local strategies to achieve a country's NDC. In South Korea, guidelines have been established to facilitate the consistent development of provincial emissions reduction strategies. But the guidelines lack clarity in terms of institutional elements: i) sectoral coverage, and ii) accounting method of greenhouse gas emissions. The primary goal of this study is to show that provincial strategies significantly depend on those two institutional elements. This study examines two scenario sets: i) including or excluding electricity and industrial sectors, and ii) direct or indirect emissions based on a NDC base storyline. For this purpose, we selected GCAM-Korea, a version of the Global Change Analysis Model specifically designed to work at the provincial level in Korea. Simulation results show that those two institutional elements play important roles in evaluating subnational emissions reduction potential. For example, in Chungcheongnam-do, a province in South Korea, the reduction rate from 2018 to 2030 is 53.9%, including the power and industrial sectors. However, when excluding these two sectors, the reduction rate significantly falls to 10.1%. For Gyeonggi-do, the reduction rate based on direct emissions is 9.3%, but it significantly increases to 28.6% when considering indirect emissions. The absence of well-defined methods may result in provinces adopting ineffective and disparate emissions reduction approaches, thereby jeopardizing the attainment of the national target. Consequently, to avert any failure in meeting the national emissions reduction target, it is crucial to furnish uniform and definitive guidelines to all local governments. This approach will ensure a cohesive effort towards greenhouse gas reduction throughout the country.
Keywords: Collective action; Collective action problem; Emission reduction; Industrial sector; Integrated assessment; Intergovernmental panel on climate changes; Provincial strategy; Reduction rate; South Korea; United nations framework convention on climate changes; Collective action problem; Emissions reduction; Integrated assessment; Provincial strategy; South Korea